2010
DOI: 10.1007/s10734-010-9385-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between financial aid availability and the college dropout rates in Colombia

Abstract: The main objective of this study is to estimate the association between financial aid and college dropout rates of postsecondary students in Colombia. We use a unique dataset from the Colombian Ministry of Education that includes all enrolled college students in the country between 1998 and 2008. Logistic regression is used to identify the correlation between receiving different forms of financial aid on the dropout rates of the students. The main results of the study suggest that the probability of dropping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
0
11
0
6
Order By: Relevance
“…For instance, the Free education introduced in South Africa in some areas enabled poor parents to enroll their children in school (Boatman & Long, 2016;Blanco & Meneses, 2010;Dynarski & Scott-Clayton, 2013;Garlick, 2013;Melguizo, 2011 andTaryn &Claudia M. 2012). Other studies also found funding to be useful in improving the academic performance of students.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Free education introduced in South Africa in some areas enabled poor parents to enroll their children in school (Boatman & Long, 2016;Blanco & Meneses, 2010;Dynarski & Scott-Clayton, 2013;Garlick, 2013;Melguizo, 2011 andTaryn &Claudia M. 2012). Other studies also found funding to be useful in improving the academic performance of students.…”
Section: Introductionmentioning
confidence: 99%
“…Este sesgo se produciría debido a que la población que accede al sistema no puede considerarse como una muestra aleatoria de la población potencial. Además del problema de selección de muestra, numerosos estudios evidencian el problema de endogeneidad presente en las ayudas estudiantiles, ya sea para estudiar el acceso o la deserción del sistema universitario (Cameron, 2009;Meneses y Blanco, 2010;Melguizo et al, 2011). Sesgo producido principalmente por la selección no aleatoria para obtener una ayuda estudiantil.…”
Section: Uno De Los Modelos Teóricos Es El Deunclassified
“…Dentro de los modelos econométricos, los más utilizados son los modelos probabilísticos (Barrios F., 2011), donde se mide la probabilidad de desertar, controlando por una serie de variables explicativas, obteniendo así su contribución marginal en la ecuación de interés (Stratton et al, 2008;Cameron, 2009;Melguizo et al, 2011). Siguiendo esta línea, algunos estudios empíricos como el de Stratton, O'Toole y Wetzel (2008) muestran cómo el no diferenciar la deserción temporal de la permanente puede llevar a la obtención de coeficientes sesgados, debido a que existen diferencias significativas entre sus factores determinantes.…”
Section: Deserción Educacionalunclassified
See 1 more Smart Citation
“…Several studies have investigated the nature and predictors of university dropout among students in a bid to inform appropriate interventions. The conclusion from these studies is that the determinants of dropout are many and complex with little consensus on which combination of factors is important (Tinto, 1975;Stratton et al, 2008;Melguizo et al, 2011;Ortiz and Dehon, 2013;Heublein, 2014;Bernardo et al, 2016;Contini et al, 2018;Mabel and Britton, 2018). For instance, Tinto's (1975) seminal student integration model proposed a complex array of risk antecedents encompassing students' pre-entry attributes, goals and commitments, as well as academic and social experiences at university.…”
Section: Introductionmentioning
confidence: 99%